Behavioral Accounting Aspects in Profit Planning and Budgeting - Sitanggang, Devi Romauli Br; Silaban, Naomi Putri Sion; Apriyanti, Pasca; Megawati, Putri; Suryadi, Nanda (Research in Accounting Journal (RAJ), 2023)
The behavioral aspect of the budget relates to the human behavior involved when the budget is prepared and implemented. This study aims to determine the aspects that exist in profit planning and budgeting and also to find out about how it is applied to the theoretical system in behavioral accounting. In conducting this research, the writer uses a descriptive method. Descriptive research is a research method that describes the characteristics of the population or phenomenon being studied. The results of this study are that we are able to understand aspects of behavioral accounting in profit planning and budgeting.